HIGH ORDER THINKING SKILLS (HOTS) DALAM PENDIDIKAN AGAMA ISLAM BERBASIS NEUROSAINS - Rani Lestari; Suyadi Suyadi (Tadrib: Jurnal Pendidikan Agama Islam, 2021)
During this time, Islamic religious education learning with the dominant learning model memorization. The memorization method is not a good one to apply, it's just that causes the student's mindset to stagnate / not develop because it only accepts what is given by the teacher. This study discusses developing students' thinking in the classroom by applying High Order Thinking Skills (HOST) specifically to Islamic religious education subjects (PAI). Then, how is the development of brain function developed during the development process. The thinking skills of students in the classroom are obtained through the process of learning from various kinds of lessons, Islamic education is no exception. The method used in this research is qualitative research with library research. The results of this study are students are able to break the way of thinking long afterwards able to reach the level of unusual thinking, critical and creative thinking which in other terms is called the ability to Higher Order Thinking Skills (HOTS).